Enhanced sensitivity of zinc phthalocyanine-based microporous humidity sensors by varying size of electrode gaps (SCOPUS) - Nur Adilah Roslan (Tanjung Malim, 2021)
Enhanced sensitivity of zinc phthalocyanine-based microporous humidity sensors by varying size of electrode gaps (SCOPUS) by Nur Adilah Roslan